Penanggulangan depresi lansia pascaerupsi Gunung Merapi melalui permainan humor berbasis kearifan budaya lokal pada kader yandu lansia - Sumarni Sumarni; Triwirasto Triwirasto; Andrian Fajar Kusumadewi; Santi Yuliani; Dwi Dwi; Nanda Kusumaningrum (Journal of Community Empowerment for Health, 2019)
Mental health of elderly is a main priority which should be concerned of, in order to provide strength to obtain welfare in old age. Merapi eruption was a natural disaster that provided long-term psychological effects on elderly survivors. It is necessary to be handled with continuous support related to depression and life quality of elderly after Merapi eruption by providing training on humor games based on local cultural wisdom and management of depression in elderly in the manner of social spiritual to the cadres of integrated services for elderly in Hunian Tetap (Huntap) Kuwang, Cangkringa, Sleman, Daerah Istimewa Yogyakarta (DIY).  Data used in this research was secondary data taken from community service that conducted in May - September 2014. The community service involved 30 cadres of integrated services for elderly and 45 elderly in Huntap Kuwang. Tools used in this research were module of local wisdom games completed with its equipment and module of early detection and coping with depression. The data were presented in descriptive quantitative and qualitative. After being given training on humor games based on local wisdom, there were increased average score on cadres’ knowledge of humor games based on local wisdom (from 66.4 to 93.2.) and skill (from 64.1 to 87.6,) as well as knowledge of early detection of depression (from 47.6 to 84.4) and skill of social support providing (from 35.3 to 80.8). There were declining trend of depression in elderly from 36 people before training to 17 people after the training of humor games based on local wisdom and spiritual social support. Training on humor games based on local wisdom and early detection of depressive tendencies along with the coping to the cadres of integrated services can reduce depressive tendencies and improve life quality of elderly in Huntap Kuwang, Cangkringan, Sleman, DIY.